The Islamic Energy Garden (IEG) Framework for Sustainable Living in Malaysian University Campuses Based on Maqasid Shariah - Madihah Mat Idris; Elina Mohd Husini; Azman Ab. Rahman; Nasrudin Sharkawi (Department of Theology and Philosophy, UKM, 2025)
Index (Tier 2)